Processos e ferramentas para o desenvolvimento de software livre: um estudo de caso - Silva, Bruno Carreira Coutinho (2006)
Free Software is more and more earning space in software market. Nowadays, there are several projects of this kind in progress around the world. This new software development model brings along a new philosophy, affecting many of the software industry principles. Despite of its importance and growth, in most cases, free software development is not being done according to the best practices of Software Engineering. In this scenario, many times software processes are not formally defined. This paper discusses an effort for defining a standard process for free software projects at LabES/UFES. The initial goal of defining these processes is to apply it in ODE´s Project, a project that aims to develop a software engineering environment as a free software The goal of this work is to define an infrastructure to support free software projects at LabES/UFES, which includes standard software processes for open source software projects, as well as the definition of requirements for the development of an environment that is able to support the processes defined. This infrastructure is to be applied to ODE Project, a project that aims to develop the software engineering environment ODE (Ontology-based software Development Environment) as a free software, giving rise to the Free ODE Project. ODE Project aims to develop a Process Centered Software Development Environment and it is the main project in progress in the Software Engineering Laboratory of the Federal University of Espírito Santo (LabES/UFES).